Attentional capture by angry faces in girls who self‐injure: Evidence from steady state visual evoked potentials. Issue 6 (15th August 2022) - James, Kiera M.; Miskovic, Vladimir; Woody, Mary L.; Owens, Max; Connolly, Evan; Gibb, Brandon E.
Abstract: Background: Non‐suicidal self‐injury (NSSI) is a significant public health concern, not only because of the personal and social cost of the behavior itself, but also because it increases risk for future self‐injurious behaviors, including suicide attempts. NSSI is increasingly prevalent during adolescence, which highlights the need for research aimed at identifying modifiable risk factors that can be targeted to reduce future risk. Building from theoretical models that highlight interpersonal processes, this study examined whether adolescents with an NSSI history exhibit greater difficulty inhibiting attention to emotionally salient interpersonal stimuli (face), indexed via steady state visual evoked potentials (SSVEPs), which provide a direct neural index of the ability to inhibit attention to task‐irrelevant stimuli. Methods: Adolescent girls aged 13–17 with ( n = 26) and without ( n = 28) an NSSI history completed a change‐detection computer task during which frequency‐tagged SSVEPs were used to assess adolescents' ability to inhibit attention to affectively salient stimuli from spatially superimposed targets. Results: Compared with adolescents with no NSSI history, adolescents with NSSI demonstrated difficulty inhibiting attention to angry adult faces. Conclusions: These findings underscore specific deficits in attentional filtering among girls with an NSSI history, which, if replicated and extended, could be a promising intervention target for reducing risk for future NSSI.